1995
DOI: 10.1111/j.1600-0897.1995.tb00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Fertility Among Women With Recurrent Spontaneous Abortions—The Effect of Paternal Cell Immunization Treatment

Abstract: Women whose only prior complaint was RSA were not at high risk for secondary infecundability, and immunization did not alter either conception rates or time to conceive. Postponement of immunization until after conception did not affect live birth rates for women selected for study because they did not have a history of prior infecundability or early repeated miscarriages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…When the analysis was done to include the five patients undergoing IVF, the significance increased to P Ͻ 0.005. The overall pregnancy success rate (65%) in patients with RSA was similar to that seen in other studies (19,20).…”
Section: Resultssupporting
confidence: 74%
“…When the analysis was done to include the five patients undergoing IVF, the significance increased to P Ͻ 0.005. The overall pregnancy success rate (65%) in patients with RSA was similar to that seen in other studies (19,20).…”
Section: Resultssupporting
confidence: 74%
“…Cowchock et al reported a better result with immunization early in pregnancy. 15 Immunotherapy might react to decidual T-cell recognition of trophoblast and induce a Th2 shift leading to maintain pregnancy. Moreover, they counted the cases, which did not achieve pregnancy in 12 months after immunotherapy, as a failure.…”
Section: Resultsmentioning
confidence: 99%